Cognition Without Neural Representation: Dynamics of a Complex System - Hipólito, Inês (Frontiers in Psychology, 2022)
This paper rejects the brain-computer metaphor. The metaphor implies that the properties of models construed in computational cognitive neuroscience (e.g. information, representation, etc.) are also expected to exist in the system being modelled (e.g. the brain). Computational models are essential tools to test a theory about how the collected data (e.g. behavioural or neuroimaging) has been generated. While the usefulness of computational models is unquestionable, it does not follow that neurocognitive activity should literally entail the properties construed in the model (e.g. information, representation). Non-cognitivist accounts of neurocognitive activity work with well-established scientific tools and coherent philosophical frameworks that resist the metaphor. After surveying the two main streams of research on neuroimaging and explaining why the metaphor is problematic, the paper focuses on a dynamical causal model of neuronal activity that combines dynamical systems theory (DST) with the theoretical insights provided by Embodied and Enactive Cognitive Science (EECS) that is consistent with the well-established network neuroscience and neuronal connectivity evidence.